Survey of Antibiotic-Resistant Bacterial Species in Hospitals in Maysan Governorate (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
spans ages 15-60, highlighting the broad impact of this pathogen. The antibiotic resistance of Enterobacter aerogenes, Pseudomonas aeruginosa, Klebsiella pneumonia to" Meropenem Amikacin, Gentamycin ,Ciprofloxacin ,Tigecycline ,Trimethoprim , Piperacillin , Cefazolin Cefoxitin, Ceftazidime ,Ceftriaxone ,Cefepime , Imipenem Levofloxacin ."This study investigates the prevalence and antibiotic resistance of three major bacterial pathogens - Pseudomonas aeruginosa, Enterobacter aerogenes, and Klebsiella pneumoniae - in hospital settings in Maysan Governorate. Pseudomonas aeruginosa was identified as highly resistant to multiple antibiotics, complicating treatment protocols. Similarly, Enterobacter aerogenes and Klebsiella pneumoniae showed significant resistance levels, for all above antibiotic except Tigecycline ,while Pseudomonas aeruginosa showed resistance for all above antibiotic . underscoring the need for stringent antibiotic stewardship and infection control measures. The findings emphasize the critical importance of addressing antibiotic resistance to ensure effective treatment options remain available and to mitigate the substantial burden on healthcare systems.